System Usability Scale (SUS) Model in Evaluating Internal Quality Audit Systems for Accreditation Process Optimization - Irawan, Yudie; Suryani, Fitri Budi; Wanabuliandari, Savitri; Muzid, Syafiul (Politeknik Negeri Batam, 2025)
The usability of internal quality audit systems plays a crucial role in ensuring the effectiveness of academic governance in higher education institutions. This study evaluates the usability of an internal quality audit system using the System Usability Scale (SUS) framework. The findings reveal a mean SUS score of 72.4, indicating good usability but highlighting key areas for improvement, particularly in navigation, interoperability, and data management workflows. A comparative analysis with previous research shows that while the system performs better than some older academic management systems, it still lags behind general academic information systems. Based on user feedback, recommendations for interface redesign, system integration, and workflow optimization are proposed to enhance overall usability. Future research should focus on user-centered design improvements, AI-driven automation, and broader system interoperability to further refine the effectiveness of quality audit processes in higher education institutions.